The mechanism of Fe induced bond stability of uranyl(v). Issue 37 (17th August 2022) - Vitova, Tonya; Faizova, Radmila; Amaro-Estrada, Jorge I.; Maron, Laurent; Pruessmann, Tim; Neill, Thomas; Beck, Aaron; Schacherl, Bianca; Tirani, Farzaneh Fadaei; Mazzanti, Marinella
Abstract : The role of Fe in the increased stability of uranyl(v ) is clarified by using state of the art uranium metalorganic chemistry, advanced X-ray spectroscopic approaches and computations. Abstract : The stabilization of uranyl(v ) (UO2 1 + ) by Fe(ii ) in natural systems remains an open question in uranium chemistry. Stabilization of U V O2 1+ by Fe(ii ) against disproportionation was also demonstrated in molecular complexes. However, the relation between the Fe(ii ) induced stability and the change of the bonding properties have not been elucidated up to date. We demonstrate that U(v ) – oaxial bond covalency decreases upon binding to Fe(ii ) inducing redirection of electron density from the U(v ) – oaxial bond towards the U(v ) – equatorial bonds thereby increasing bond covalency. Our results indicate that such increased covalent interaction of U(v ) with the equatorial ligands resulting from iron binding lead to higher stability of uranyl(v ). For the first time a combination of U M4, 5 high energy resolution X-ray absorption near edge structure (HR-XANES) and valence band resonant inelastic X-ray scattering (VB-RIXS) and ab initio multireference CASSCF and DFT based computations were applied to establish the electronic structure of iron-bound uranyl(v ).